Minimum sprite plasma density as determined by VLF scattering. - Dowden, Richard L.; Rodger, Craig J.; Nunn, David
The scattering of VLF sub-ionospheric transmissions by sprite plasma through horizontal angles up to 180° shows that sprite plasma is highly conducting. Following a simple transmission-line (one-dimensional-wave) model in 1997, two-dimensional and three-dimensional models have been produced. Here, we compare the results of the three models, and show that all require a uniform conductivity of at least 30 μS/m, corresponding to an electron density at 70 km altitude of ~1010 m-3 (~104 electrons per cc), and so about 105/cc at 55 km. The latter ionization density is about that of the daytime E-region, and over six orders of magnitude above the ambient density at 55 km. By contrast, the ?early/fast? events, as defined by the Stanford group, do not exhibit scatter angles above 15°, suggesting that the sprite conductivity rises too slowly (as the plasma cools) to reach adequate backscatter within the time allowed by the ?early/fast? definition.
Keywords: Red sprites; VLF; Electromagnetic propagation; Electromagnetic propagation in plasma media; Electromagnetic scattering; Electromagnetic scattering in plasma media; Conductivity measurement; Plasmas; Ionization; Direction of arrival estimation